Fraternity, Gift and Reciprocity in Caritas in veritate (Cultura Económica, 2019)
The author explores in this article the extrapolation of the principle of fraternity to the economic level in the Encyclical of Benedict XVI. Old dichotomies such as the division between the economic and the social spheres should be overcome. It is necessary to think a new welfarein which the search for profit and the social concern may arise in an integrated way. In conclusion, the author stresses the importance of the principles of gift and reciprocity in order to guide the economy towards a global governance that combines goods of gratuity with goods of justice.
Keywords: fraternity; welfare; gift; reciprocity; global governance